PERSEPSI SISWA SMA NEGERI 1 WAY TENONG TERHADAP SITUS BATU BERAK SEBAGAI SUMBER BELAJAR SEJARAH - Anton Saputra; Sumiyatun Sumiyatun (Swarnadwipa, 2017)
Many sites Evolving at the Lampung Barat and Area, but Yang heard many stone Berak is a site, the site Berak rock is story is owned by society Pura Jaya, Cane Garden. Sites Are A Source Berak stone relics of megalithic Yang is fixed, and the rock sites berak managers not for profit hearts Serving society. Learning is part of Student Needs. The study findings in getting maximum of necessary facilities and infrastructure favor, among them is a source of learning. In history lesson, not just learning resources obtained from guru explanation and lesson books-only, but also can be obtained on the site berak stone as a medium of Learning the number available, namely site berak stone. The existence of the site Berakstone, can be used by students and teachers of history because many collection sites berak stone very relevant with lesson material sejarah.In The issues discussed research hearts singer is how perception students SMA Negeri 1 Way Tenong Against Berak stone sites as a source of learning History. Purpose of Research Singer is (1) to review perception students know SMANegeri 1 Way Tenong against berak stone sites as a source of learning history, (2) to review the constraints Students know the hearts utilize the site Berak stone as a source of learning history.Research singer using qualitative method with take location study in SMANegeri 1 way tenong, informants hearts research singer is a student of smanegeri 1 way Tenong, engineering hearts data collection research singer several methods using, (1) observation, (2) interview (3) method literature, (4) documentation, (5) questionnaire. analysis of data used (1) data reduction, (2) data presentation, (3) the withdrawal conclusion.Results Singer, (1) Are students already understand stone sites berak as a relic of megalithic and can be used as a source of learning history, (2) are also students not yet understand stone sites berak as relics on megalithic and assume stone sites Berak as Points Recreation, (3) the constraints facing Students Now it's hard to review a visit Ke stone sites berak because factor transport because not all Students have the Personal Vehicle and must issued covers the cost not least because Must Rise ojek.